Dialect of Rahovec and the sorrounding area - Dulaj, Fridrik; Duraj, Petrit (Technium Social Sciences Journal, 2023)
The Project "The dialect of Rahovec and the surrounding area" is fifteen years work of dialectologists and sociolinguistics issues of this area. During the description of linguistic situation of Rahovec area, we have found linguistic meeting points with those of whole north-east gege dialect. The best matches have been found in Ratkoc’s areal. Whereas in two other areala, Rahovec and Krusha, we have come across with some differentiating points, whether in phonetic, morphologic or syntactic occurrences, which have been handled in the paper. Thus the level of nasality, which comes across differently between two areala of this area.